Cinnamon: A Multifaceted Medicinal Plant - Pasupuleti, Visweswara Rao; Siew, Hua Gan (Hindawi Publishing Corporation, 2014)
Cinnamon (Cinnamomum zeylanicum, and Cinnamon cassia), the eternal tree of tropical medicine, belongs to the Lauraceae family. Cinnamon is one of the most important spices used daily by people all over the world. Cinnamon primarily contains vital oils and other derivatives, such as cinnamaldehyde, cinnamic acid, and cinnamate. In addition to being an antioxidant, anti-inflammatory, antidiabetic, antimicrobial, anticancer, lipid-lowering, and cardiovascular-disease-lowering compound, cinnamon has also been reported to have activities against neurological disorders, such as Parkinson’s and Alzheimer’s diseases. This review illustrates the pharmacological prospective of cinnamon and its use in daily life.